"Covid Cure (1)": Anas's Investigative Journalism and the Ethics of Uncovering Fakes in African Spaces. Issue 3 (3rd July 2021) - Atuire, Caesar A.; Addison, Grace; Owusu, Samuel Asiedu; Kingori, Patricia
ABSTRACT: Investigative journalists sometimes resort to the use of fake identities in order to reveal fakes and malpractice, a phenomenon that can be described as revelatory fakery. Acclaimed investigative journalist, Anas Aremeyaw, in collaboration with BBC Africa Eye, employs revelatory fakery to expose and prosecute wrongdoers in Ghana. From an ethical viewpoint, Anas's revelatory fakery, a second order fakery, becomes a seedbed for an exponential level of fakery. This article poses the question whether Anas's work is journalism or instead yet another expression of fakery that allows a prosecutor to act as a journalist. This question is contextualised within the ethics of the broader narratives created by the BBC Africa Eye investigations, which feed and promote a spectacular but "fake" narrative about Africa as a place of negatives, difference, and darkness.